أسس التفسير المقاصدي للقرآن الكريم وتطبيقاته على الكليات الخمس في تفسير التحرير والتنوير للطاهر ابن عاشور /‏ - قائد، نشوان عبده خالد
This study is aimed at highlighting the main features of the branch of Qur'anic exegesis (tafsir) that focuses on the purposes of the Qur'an (maqasid). This is done by way of establishing a methodological framework that helps define the type of tafsir based on maqasid of the Qur'an, tracing its historic roots, and clarifying the differences between it and other types of tafsir. The study also lays down the objective foundations and establishes an academic methodology related to the maqasid that are the concern of this type of tafsir. It also highlights the reflections of those methodological foundations upon the five necessities of the Shari'ah, (al-kulliyyat al-khams) considering them to be among the most fruitful areas for applying the maqasid of the Qur'an. The study uses Tafsir al-tahrir wa al-tanwir by al-Tahir ibn Ashur as a springboard for that, based on its status as a pioneering work in the revitalization of tafsir that combines mastery of the classic Islamic legacy and worldview with an awareness of modernity. The author applies maqasid to tafsir according to the theoretical parameters he calls for in the preface to his tafsir. He then provides a practical demonstration of them in the tafsir itself, bringing out the sweetness of the Qur'anic text and its effectiveness in bringing about social change. The researcher has adopted both inductive and analytic methodologies as the basis for treating this topic in order to develop a solid theoretical basis for understanding maqasid-based tafsir and striving for a comprehensive treatment of the topic and an understanding of its axioms. It is found that: The most prominent characteristic that distinguishes maqasid-based tafsir from other tafsir methodologies is its highlighting of the secrets, wisdom, meanings and objectives contained in the verses of the Qur'an and making them a primary element of the tafsir. Also, applying the fundamentals of maqasid-based tafsir to the five necessities of the Shari'ah (al-kulliyyat al-khams) represents a promising development in establishing a solid basis for this type of tafsir. This becomes discernible in the course of linking the various types of maqasid with their textual bases in the Qur'an in accord with an academic methodology that the researcher calls the methodological foundations for maqasid-al-Qur'an-based tafsir. Also, Tafsir al-tahrir wa al-tanwir is one of the most important contemporary tafsirs that has attempted the revitalization of Islamic civilization by presenting the Qur'an as guidance and revealing its noble objectives. It stands out in its precise conveyance of the historical legacy, in exercising independent legal judgment, and in its creativity in employing the maqasid.